UPAYA PENINGKATAN OMSET PENJUALAN UKM KERIPIK TEMPE DESA TEMPURAN KABUPATEN NGAWI MELALUI PELATIHAN DIGITAL MARKETING - Susanto, Lukas; Astuti, Indra Puji; Mumtahana, Hani Atun; Wikanso, Wikanso; Primiani, Cicilia Novi (Jurnal Abdi Insani, 2024)
The aim of this community service is to increase the sales volume and turnover of UKM tempeh chips by utilizing digital marketing in Tempuran Village, Paron District, Ngawi Regency. The activity method is carried out in the following stages: 1) Survey/field observation, 2) Socialization/counseling, 3) Training and mentoring, 4) Monitoring and evaluation. The targets of the service activities are 15 UKM’s of tempeh chips. Data collection techniques were carried out using observation, questionnaires and interviews related to sales turnover and marketing production volume of tempeh chips through digital marketing. Data analysis was carried out descriptively. Based on data analysis, sales turnover before training averaged 72.74%. Sales turnover after training averaged 95.47%. The average value of increase in sales turnover is 23%. The training participants were enthusiastic and satisfied with participating in the training activities. The conclusion of the service activity is that the use of digital marketing can increase the sales turnover of tempeh chips in Tempeh Village UKM tempeh chips.